A Framework for Ex-Ante Economic Analysis of Tourism Investments: An Application to Haiti - Onil Banerjee; Martin Cicowiez; Sebastien Gachot (Inter-American Development Bank (IDB), 2015)
This study develops a linked regional computable general equilibrium and micro-simulation (RCGE-MS) model to assess the regional economy-wide and poverty impacts of a US36 million investment in tourism in the south of Haiti. The first social accounting matrix for Haiti with a base year of 2012/2013 was constructed to calibrate the model. This research addresses three key gaps identified in the tourism impact assessment literature. First, a destination-specific tourism demand and value chain analysis was used to calibrate the shocks implemented in the model. Second, the RCGE-MS approach moves beyond the representative household configuration to enable more robust analysis of tourism investment impacts on poverty and income inequality. Third, results of this modelling were used to inform a social cost-benefit analysis to provide greater transparency in the evaluation of trade-offs between investment alternatives. Results of this analysis showed a positive impact on sectoral activity, especially for the hotel and restaurant sector (182.1% in 2040) and a 2.0% increase in Gross Regional Product by 2040. The South's exports fell 4.7% below baseline and imports were 6.1% higher due to the inflow of foreign exchange, the appreciation of the regional real exchange rate, increased demand for most goods and services, and limited regional productive capacity. The rate of unemployment fell from 26% to 23%. The investment helped lift some of the regions poorest out of poverty, reducing the poverty headcount by 1.6 percentage points. Driving this result was an increase in employment, wages and non-labor income. The linked RCGE-MS approach proves to be a powerful tool for assessing how tourism investments affect regional economic activity and revealing the mechanisms through which tourism can contribute to increased employment opportunities and poverty reduction.
hdl:11319/7238
Keywords: C68; D61; R13; O12; O15; F21; 330; Computable General Equilibrium; CGE; Tourism Investment; Regional Welfare; Poverty; International Investment; Benefit Cost